Do the village financial system application and quality of financial reports in Kediri regency matter? - Nisa Mutiara; Eka Askafi; Wawan Herry Setyawan (Jurnal Inovasi Ekonomi, 2022)
The study aimed to determine how implementing the Village Financial System (Siskeudes) application affects transparency as a mediator in realizing quality village financial reports in Kediri Regency. The quantitative research used secondary data as a questionnaire to the Village Treasurer in Kediri Regency. Purposive sampling was used to carry out the sample selection process, and 343 villages provided 185 samples for the study through a regression model. The results show that the Siskeudes application can directly affect the quality of village financial reports and indirectly through transparency as a mediating variable. The Siskeudes application significantly impacts the caliber of village financial reports; transparency can augment this impact as a mediating factor.